Metodologias sintéticas envolvendo reações fotoquímicas e eletroquímicas em condições de batelada e fluxo contínuo - Silva, Rodrigo Costa e (2023)
SYNTHETIC METHODOLOGIES INVOLVING PHOTOCHEMICAL AND ELECTROCHEMICAL REACTIONS IN BOTH BATCH AND CONTINUOUS FLOW CONDITIONS. Initially (Chapter 1), general aspects of the studied reactions were presented and in the chapter 2, a methodology for the photoarylation of diazines with aryldiazonium salts was described. This reaction was promoted by visible light in the absence of a photocatalyst. The diazines (pyrazine, pyrimidine and pyridazine) were arylated from 69 to 84% yield and UV-Vis spectroscopic studies demonstrated that the individual components of the mixture were not photoactive while irradiated by visible light, but the reaction was promoted by a photoactive aggregate formed between the donor (diazines) and acceptors species (aryldiazonium salts) in solution, so-called as EDA complex. However, aspects related to the formation of EDA complexes in solution and some limitations of the methodology were observed. Alkylation reactions with alkyldiazonium salts have not been evaluated for safety reasons. Furthermore, the reaction required a large excess of diazines and was not regioselective with no advantages to be transposed to continuous flow conditions. Given the above, a methodology for the selective C–4 alkylation of pyridines under continuous flow was developed (Chapter 3). The UV irradiation of benzophenone in the presence of alkanes, promoted the formation of alkyl radicals by the hydrogen atom transfer (HAT) process. The radicals reacted with a protected pyridinium salt, and the product was formed after deprotection using base. All the transformations were carried out under continuous flow in only 15 minutes residence time. Using deactivated and functionalized alkanes, both substituted and unsubstituted pyridines were alkylated from 23 to 71% yield. Mechanism studies suggested that benzophenone promoted the generation of alkyl radicals and oxidation of the radical intermediate. In Chapter 4, aspects related to the formation of EDA complexes in solution were evaluated and a methodology for the accelerated discovery of EDA-mediated reactions was developed. Overall, an algorithm employing image processing techniques was developed. The image-processing algorithm evaluated the color change after mixing the components, analyzed thin-layer chromatography plates and classified 1225 mixtures. The algorithm classified i) 1117 mixtures as without color change; ii) 45 mixtures as colorimetric reactions; iii) 30 mixtures as possible EDA, but without evidence of products after irradiation, and iv) 33 mixtures as possible EDA-mediated reactions. The algorithm identified that irradiation of the mixture containing triphenylphosphine and 4-nitrophthalonitrile produces the corresponding iminophosphorane via the EDA complex, thus revealing a new photocatalyzed chemical transformation. A small library of compounds was produced after reaction optimization. However, the optimized photochemical conditions, 48 hours at -20 °C, were considered impractical. In this way, a methodology for the electrochemical synthesis of iminophosphorane under continuous flow conditions was developed (Chapter 5). Acid-catalyzed chemoselective reduction of nitroaromatics in the presence of triphenylphosphine produced iminophosphoranes in up to 92% yield at room temperature and in only 5 minutes of residence time. Nitroarenes substituted with nitriles, aldehydes, ketones, esters, and triflate were compatible with the electrochemical conditions used. Mechanism studies suggested the formation of intermediate nitrenes generated via sequential-paired electrolysis. Finally, iminophosphoranes were also used in other synthetic protocols. Aldimines and amines were obtained by the aza-Wittig and Staudinger reduction reactions, respectively.